The Views of Family Health Worker in the Subsidiary Health Centers of University on the Determinants of Cesarean Section without Medical Indication - Ali-Asghar Kolahi; Naria Abolghasemi; ّFarima Mohammadi; Farnaz Ehdaeivand (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Increasing rates of cesarean section (C/S) in many countries hah caused health officials concern. In our country cesarean sections without medical indication is a thread for health system. This study aimed to determine the views of family health unit staffs of health centers regarding cesarean sections without clinical indication in 2014. Materials and Methods: This Cross-Sectional study was conducted in 2014 in Tehran, Iran. The study population included all employees of family health units working in health centers affiliated to Shahid Beheshti University of Medical Sciences and Health Services. A total of 739 patients were available for sampling. Data was collected using a self-administered questionnaire. Results: In health workers view the cause of were as follows respectively: mother request 336 (45.5%), gynecologist recommendation due to nonmedical indications 234 (31.7%) and gynecologist recommendation due to medical indications 169 (22.8%). The most causes of without medical indication were mother's fear of labor pain, the cost benefit of C/S, lack of mother's Knowledge regarding C/S adverse effects, convenience of performing C/S for gynecologist and having health insurance especially supplementary insurance, respectively. Conclusion: The study showed that the necessity of mothers and their families education regarding the methods of labor pain control and the adverse effects of C/S.